2018
DOI: 10.1021/acs.jpcc.7b10900
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-Layer Assemblies of Coordinative Surface-Confined Electroactive Multilayers: Zigzag vs Orthogonal Molecular Wires with Linear vs Molecular Sponge Type of Growth

Abstract: Surface-anchored coordination-based molecular assemblies (CBMA) are very powerful tools for the design of modern materials. The CBMAs were created using bis-terpyridine–iron coordination chemistry by the alternation of linear or bent bis-terpyridine ligands and Fe­(II) metal centers. The coordination of the bent ligand results in the formation of zigzag structures that experience linear growth with each successive deposition step. Interestingly, the deposition of the linear ligand has two distinct steps. Durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Electrosynthesis is rapid (1 min for each addition), and possibly independent of metal species and organic ligands of complexes, thus they provide significantly high controllability toward uniform synthesis, compared to well-known method based on coordination chemistry. To date, the iterative synthesis of organometallic polymers were mostly achieved by the metal coordination between almost Fe 2+ and terpyridine on solid substrate, which took up to 24 h for each addition of single monomer at room temperature [26][27][28] . Absorption laying at 505 nm is attributed to metal-to-ligand [Os II (dπ) to tpy(π*)] charge transfer (MLCT) transition, while the additional band at 680 nm seems to be owing to spin-forbidden MLCT transition from 1 [Os II (dπ) 6 ] to 3 [Os II (dπ) 5 tpy(π*) 1 ] 29 .…”
Section: Iterative Electrosynthesis Of Homo-organometallic Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrosynthesis is rapid (1 min for each addition), and possibly independent of metal species and organic ligands of complexes, thus they provide significantly high controllability toward uniform synthesis, compared to well-known method based on coordination chemistry. To date, the iterative synthesis of organometallic polymers were mostly achieved by the metal coordination between almost Fe 2+ and terpyridine on solid substrate, which took up to 24 h for each addition of single monomer at room temperature [26][27][28] . Absorption laying at 505 nm is attributed to metal-to-ligand [Os II (dπ) to tpy(π*)] charge transfer (MLCT) transition, while the additional band at 680 nm seems to be owing to spin-forbidden MLCT transition from 1 [Os II (dπ) 6 ] to 3 [Os II (dπ) 5 tpy(π*) 1 ] 29 .…”
Section: Iterative Electrosynthesis Of Homo-organometallic Polymersmentioning
confidence: 99%
“…29). Usual chemical coordination for synthesis of organometallic wires [26][27][28] requires the high-quality solvents without external ions for synthesis and purification, and its controllability and reproducibility still remain stagnant and challenge in general metal and ligand species, and following coordination types for further sequence-controlled synthesis. Each addition of monomer for stepwise chemical coordination generally took very long time up to 24 h, which could cause the depolymerization and exchange of ligands and metal cores during the synthesis of organometallic polymers 34 .…”
Section: Iterative Electrosynthesis Of Homo-organometallic Polymersmentioning
confidence: 99%
“…V‐tpy‐Mn N1s spectrum (Figure S3B) displays a signal at 399.2 eV characteristic to the pyridinic nitrogen atoms in the metal‐tpy mono‐complexes [33,45,49] . Mn2p 1/2 and Mn2p 3/2 peaks were observed at 654.0 eV and 641.9 eV that is typical for Mn 2+ [50] .…”
Section: Resultsmentioning
confidence: 99%
“…[33] V-tpy-Mn N1s spectrum ( Figure S3B) displays a signal at 399.2 eV characteristic to the pyridinic nitrogen atoms in the metal-tpy mono-complexes. [33,45,49] Mn2p 1/2 and Mn2p 3/2 peaks were observed at 654.0 eV and 641.9 eV that is typical for Mn 2 + . [50] The atomic ratio of C : N : Mn is 95:0.79:0.24, this is close to the expected ratio of 3 : 1 of N:metal that would be expected for the mono-complex (1 : 1 metal-to-ligand stoichiometry).…”
Section: Physical Characterizationmentioning
confidence: 92%
“…Previously, it was demonstrated that 2,2':6',2''terpyridine (terpy) moiety can form stable complexes with a variety of metals in different oxidation states. [17][18] This moiety as a part of different ligands can be used to covalently anchor and grow electrochromic (EC) molecular wires on a flat surface [19][20] or to form EC coatings or separate nanosheets of metallo-supramolecular polymers. [21][22][23] Our group has developed ECDs that utilize just a monolayer of EC terpy-based metal complexes deposited on enhanced surface area conductive supports [24] to form the working electrode.…”
Section: Introductionmentioning
confidence: 99%